2013
DOI: 10.1080/09593330.2013.788070
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and transport ofPseudomonas aeruginosain porous media: lab-scale experiments and model analysis

Abstract: In this study, the deposition and transport of Pseudomonas aeruginosa on sandy porous materials have been investigated under static and dynamic flow conditions. For the static experiments, both equilibrium and kinetic batch tests were performed at a 1:3 and 3:1 soil:solution ratio. The batch data were analysed to quantify the deposition parameters under static conditions. Column tests were performed for dynamic flow experiments with KCl solution and bacteria suspended in (1) deionized water, (2) mineral salt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Adsorption to filter media is one of the mechanisms involved in bacteria removal from aqueous suspensions (Kwon et al, 2013). Studies have shown the possibility of adsorbing Gram-positive and Gram-negative bacteria to minerals such as quartz and corundum (Yee et al, 2000;Rong et al, 2008).…”
Section: Influence Of the Pilots Configurations On The Treatment Efficiencymentioning
confidence: 99%
“…Adsorption to filter media is one of the mechanisms involved in bacteria removal from aqueous suspensions (Kwon et al, 2013). Studies have shown the possibility of adsorbing Gram-positive and Gram-negative bacteria to minerals such as quartz and corundum (Yee et al, 2000;Rong et al, 2008).…”
Section: Influence Of the Pilots Configurations On The Treatment Efficiencymentioning
confidence: 99%